Characterization of a human 'midisatellite' sequence. - Nakamura, Y (1987)
We have examined the structure and DNA sequence of a human genomic locus that consists of a large hypervariable region made up of repeats of a simple sequence. With several restriction enzymes, the locus shows many restriction fragments that vary quantitatively as well as qualitatively. Other restriction enzymes produce only a single, high-molecular-weight fragment at this locus. Almost all of the fragments are revealed with a simple sequence probe. Southern transfers of the high-molecular-weight restriction fragments produced by the restriction enzymes NotI and SfiI, resolved by pulsed-field gel electrophoresis, gave at most two fragments, demonstrated to be allelic, showing that the majority of the restriction fragments seen in the complex patterns are at a single locus. The estimated size of the region homologous to the probe varied from 250 to 500 kilobases. DNA sequencing indicated that the region consists of tandem repeats of a 40-base-pair sequence. Some homology was detected to the tandem repeating units of the insulin gene and the zetaglobin pseudogene hypervariable regions, and to the "minisatellite" DNA at the myoglobin locus.